A Survey of Glucocorticoid Adverse Effects and Benefits in Rheumatic Diseases: The Patient Perspective. Issue 8 (December 2017) - Black, Rachel J.; Goodman, Susan M.; Ruediger, Carlee; Lester, Susan; Mackie, Sarah L.; Hill, Catherine L.
Abstract : Objective: The aim of this study was to explore, from the patient's perspective, the beneficial and adverse effects (AEs) of glucocorticoids (GCs) in patients with rheumatic diseases, to be used in the development of a patient-reported outcome measure. Methods: A cross-sectional survey, capturing benefits and AEs of GC use, was administered to 2 groups of patients: (1) those attending a tertiary rheumatology clinic with various rheumatic diseases who had used GCs within the past year and (2) patients from the Hospital for Special Surgery rheumatoid arthritis database. Results: Cohort 1 had 55 GC users, and cohort 2 had 95 GC users and 29 nonusers. The majority of GC users in both cohorts reported at least 1 AE (100%, 86%). The AE prevalence per person was 50% higher in cohort 1 compared with GC users in cohort 2 (7.7 vs. 5.3; AE ratio, 1.5; 95% confidence interval, 1.3–1.7) and 2-fold greater in cohort 2 GC users compared with GC nonusers (5.3 vs. 2.6; AE ratio, 2.0; 95% confidence interval, 1.6–2.6). In both cohorts, AEs identified as "worst" by GC users included skin thinning/easy bruising, sleep disturbance, mood disturbance, and change in facial shape. Most felt GCs helped their disease "a lot" (78%/62%) and that the benefits were greater than the AEs (55%/64%). Many AEs were more frequent in GC users than in nonusers. Conclusions: Patients receiving GC therapy for rheumatic conditions report a large number of AEs and those that have the greatest life impact are often difficult for physicians to measure. These results will inform the development of a patient-reported outcome measure to capture the effects of GCs from the patient's perspective. Abstract : Supplemental digital content is available in the text.